Kemunculan Kemunculan Rashba Splitting Intrinsik pada Monolayer Janus Si2SbBi: Studi Komputasi Berdasarkan Teori Fungsional Densitas - Affandi, Yusuf; Darojat, Yusron; Anshory, Muhammad; Masfufah, Awi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
In this paper, we investigate the electronic structure of Janus Si2SbBi monolayer and compare it with the non-polar systems Si2Bi2 and Si2Sb2 monolayer based on Density Functional Theory (DFT) calculation. According to the first-principles calculation, these systems exhibit semiconductor properties with energy gaps are 0.674 eV, 0.28 eV, and 1.13 eV for Janus Si2SbBi, Si2Bi2, and Si2Sb2, respectively. In addition, the intrinsic Rashba splitting is also observed around the Γ Point on conduction band minimum (CBM) in the electronic structure of Si2SbBi monolayer, which is not found in Si2Sb2 and Si2Bi2 monolayer systems. This Rashba splitting phenomenon we analyze by using the perturbation theory based on symmetry group and get the first-order Rashba Parameter α1=1.84 eVÅ , and α1=1.73 eVÅ , for Γ-K and Γ-M direction, respectively. With the strong intrinsic Rashba Splitting, the Janus Si2SbBi monolayer has excellent potential to be the candidate of semiconductor material for spintronics devices.